Problem Tree Analysis for Farm Communities along Bicol River Basin, Camarines Sur, Philippines - Laureta, Ricky; Baldo, Diomerl Edward; Nunag, Jessica Dionne; Gasga, Kier; Ebron, Ma. Petra (Asia Pacific Journal of Sustainable Agriculture, Food and Energy, 2022)
In the past decades, climate change has become a disruptive issue in agriculture. This paper provides a brief problem analysis of the current status of selected agricultural farmlands along Bicol River basin (BRB) in the province of Camarines Sur. Six barangays from initially identified vulnerable municipalities were assessed on their respective community’s agricultural problems. Two barangays from each from the municipality in Baao, Canaman and Minalabac, were targeted as participating sites in the Participatory Rural Appraisal (PRA). The paper aimed to survey insights into the dynamics of problems in agriculture-based problems of these communities and to identify priorities needed for the improvement of farm productivity. A problem tree analysis revealed that sixty-seven percent (67%) of the sites claimed that problem’s root cause was the absence of water source for efficient farming irrigation. Oppositely, thirty-three percent (33%) of the participating communities pinpointed the base problems to prolonged flooding that hampers the ideal farm yield. Other problems mentioned included unavailability of advanced farming technologies, low harvest rates due to climate shift, high cost of farming inputs such as fertilizers and labor, access to farm to market roads, low farm gate price of harvested products and lack of trees to aide in flood prevention. The study further revealed that either water scarcity or effects of rainfall intensities are the key problems faced by agricultural communities in the selected areas.